If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-100=x+2
We move all terms to the left:
2x-100-(x+2)=0
We get rid of parentheses
2x-x-2-100=0
We add all the numbers together, and all the variables
x-102=0
We move all terms containing x to the left, all other terms to the right
x=102
| 1/4+1/2+z=-3/4 | | 11=m–4 | | 2(39x-11)=2(17x+6) | | 39x-11=17+6 | | 39x-11=2(17x+6) | | -3/8-7x=-149/24 | | 2(39x-11)=17x+6 | | 9x+1=-1x+19 | | 14^-9x=3^x-5 | | 5x+5=2x+3+x | | -18x+14-17x=4x | | -15x+122=-8x+66 | | -8x-20=-5x-11 | | 2x-21=x-14 | | 10x+19=15x+29 | | -24x+99=-16x+51 | | -79=-1-6n | | 9p-9=18 | | 3p-6=-54 | | Y=2.3x+6 | | -12=(f-6) | | x²+8+15=63 | | 20+50x=10+5x | | 2n+1=5n= | | 12x+20=19x+18 | | -1.14x+0.26=-10 | | -9/5x-2=-20 | | 0.47x+1.24=5 | | 9/2x+5=-31 | | 6w+4=1 | | 63=7(1+4b | | 35x-25=17 |